Pelatihan Teknik Pengolahan Yoghurt Nabati Untuk Guru-Guru Smp Negeri 1 Pacet - Isrianto, Pramita Laksitarahmi; Kristianto, Sonny; Marmi, Marmi; Chamidah, Dina; Sunaryo, Sunaryo; Wilujeng, Sukian (Universitas Wijaya Kusuma Surabaya, 2023)
Yoghurt products are fermented drinks made from milk. Usually this yoghurt is a healthy drink made from fermented cow's milk. In line with developments in science and technology, sources of raw materials for yoghurt can come from other than cow's milk, namely from camels, goats, soybeans and corn. soya, soya. Many people have developed yoghurt products from animal sources, but there is still little development for yoghurt products from vegetable sources such as soybeans, soybeans, and so on. Vegetable yoghurt milk products also have high nutritional content. Yoghurt products are widely known by the public, but there are still many who do not know the simple techniques for making them on a household scale. This is actually done at home as long as it is made using the correct technology and can later be used as a business to increase income. The delivery of knowledge and training on soya yoghurt can be realized through the Community Service program carried out by the UWKS Biology Education Department. The targets of this community service activity are teachers at SMP Negeri 1 Pacet which is located in Petak village, around 28 km from Pacet. This program includes outreach activities, training, assistance with production, packaging and marketing. The results obtained from this program are that it can increase the soft skills and hard skills knowledge of teachers at SMP Negeri 1 Pacet, improve the quality of life, and increase entrepreneurial opportunities.